Drought - Impacts and Management 2022
DOI: 10.5772/intechopen.103927
|View full text |Cite
|
Sign up to set email alerts
|

Water Shortages: Cause of Water Safety in Sub-Saharan Africa

Abstract: This chapter highlights a high rate of water crisis across sub-Saharan Africa (SSA) despite its huge hydro. For example, currently, less than 2% of SSA\'s renewable groundwater is used to irrigate just about 1% of its cultivable land. Factors contributing to water stress include rainfall deficit and drought, increased water requirements, population growth, urbanization poverty. Coupled with the uneven distribution of water resources and mismanagement of water facilities, the gap between the demand for water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our study aimed to analyze the conditions of water access in the study region and has demonstrated that following studies from other African Sub-Saharan regions, more than nine households surveyed experience water shortages in the study region (Matchawe et al, 2022). The factors likely to explain this water scarcity in Kinshasa include the fact that the study was carried out in overcrowded new outskirts lacking urbanization and basic social services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study aimed to analyze the conditions of water access in the study region and has demonstrated that following studies from other African Sub-Saharan regions, more than nine households surveyed experience water shortages in the study region (Matchawe et al, 2022). The factors likely to explain this water scarcity in Kinshasa include the fact that the study was carried out in overcrowded new outskirts lacking urbanization and basic social services.…”
Section: Discussionmentioning
confidence: 99%
“…The factors likely to explain this water scarcity in Kinshasa include the fact that the study was carried out in overcrowded new outskirts lacking urbanization and basic social services. Poverty and the lack of attention by current policies lead to the failure to apply the right of access to water for all in these regions (Côrtes et al, 2016;Matchawe et al, 2022).…”
Section: Discussionmentioning
confidence: 99%